2011
DOI: 10.1002/asi.21672
|View full text |Cite
|
Sign up to set email alerts
|

Barriers to task‐based information access in molecular medicine

Abstract: We analyze barriers to task-based information access in molecular medicine, focusing on research tasks, which provide task performance sessions of varying complexity. Molecular medicine is a relevant domain because it offers thousands of digital resources as the information environment. Data were collected through shadowing of real work tasks. Thirty work task sessions were analyzed and barriers in these identified. The barriers were classified by their character (conceptual, syntactic, and technological) and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
34
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 30 publications
(34 citation statements)
references
References 42 publications
(55 reference statements)
0
34
0
Order By: Relevance
“…There is also potential for lifelogging technologies to be used by organisations as a means of recording/logging the activities of employees, for various reasons, such as logging employee activities for legal/historical reasons, replacing manual record taking, logging information access activities as in Kumpulainen et al (2009), or potentially as a new technology to support aspects of what Stein (1995) refer to as organisational memory. The idea here is to automatically capture procedures and processes for everyday activities in the workplace.…”
Section: Who Lifelogs and Why ?mentioning
confidence: 99%
See 2 more Smart Citations
“…There is also potential for lifelogging technologies to be used by organisations as a means of recording/logging the activities of employees, for various reasons, such as logging employee activities for legal/historical reasons, replacing manual record taking, logging information access activities as in Kumpulainen et al (2009), or potentially as a new technology to support aspects of what Stein (1995) refer to as organisational memory. The idea here is to automatically capture procedures and processes for everyday activities in the workplace.…”
Section: Who Lifelogs and Why ?mentioning
confidence: 99%
“…The idea here is to automatically capture procedures and processes for everyday activities in the workplace. While this tends to have more success for office environments where we log digital activities (web usage, emails, document accesses) rather than physical ones, there are examples of recent work with healthcare workers in clinical practice who have to log their work and record their clinical notes at the end of a shift, Kumpulainen et al (2009), as well as lifelogging for other job-specific tasks, Fleck and Fitzpatrick (2006). Lifelogging has also been used in market research, targeting novel qualitative analysis based on analysis of subjects' lifelogs and the amount of exposure they have to advertisements, Hughes et al (2012).…”
Section: Who Lifelogs and Why ?mentioning
confidence: 99%
See 1 more Smart Citation
“…For the sake of simplicity, however, information searching is not discussed as a separate category; issues related to barriers to information searching are reviewed under the broader concept of information seeking. However, to sharpen the focus, barriers specifically related to IR were excluded (e.g., Borgman, 1996;Kumpulainen & Järvelin, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…It is inevitable for the future biomedical domain expert to switch from the classical consumer-like role [44] to an active part in the knowledge discovery process [27,30]. However, this is not so easy, because it is well known that many biomedical research projects fail due to the technical barriers that arise to the domain experts in data integration, data handling, data processing, data visualization and analysis [1,34,43]. A survey from 2012 among hospitals from Germany, Switzerland, South Africa, Lithuania, and Albania [60] showed that only 29 % of the medical professionals were familiar with any practical application of data mining methods and tools.…”
Section: Graph-based Discovery In Medical Researchmentioning
confidence: 99%